Business Communication Ethics Training for MSMEs in Garut Regency - Lindayani, Lindayani; Setiawan, Rahyuniati; Sa’adah, Imas; Maolani, Rivaldy (Indonesian Journal of Community Empowerment (IJCE), 2025)
Lack of training and coaching in this area is a major contributing factor. In today's digital era, MSMEs are required to maintain effective communication not only in person but also through digital platforms such as social media and e-commerce. The training method used in this activity is an educational-participatory approach that positions MSMEs as active participants in the training process, not merely recipients of material. The results of this activity indicate that after the training, there were significant changes in the way participants communicate with customers and business partners. Some participants began to demonstrate a more empathetic, polite, and open attitude when handling consumer complaints. This training provides a foundation for MSMEs in Garut Regency to build reputations and customer loyalty through ethical communication. Therefore, the interactive and experience-based training program significantly supports the learning process for participants with diverse educational backgrounds and business experience.